The intrinsic reddening of the Magellanic Clouds as traced by background galaxies – I. The bar and outskirts of the Small Magellanic Cloud. Issue 3 (23rd August 2019) - Bell, Cameron P M; Cioni, Maria-Rosa L; Wright, A H; Rubele, Stefano; Nidever, David L; Tatton, Ben L; van Loon, Jacco Th; Ivanov, Valentin D; Subramanian, Smitha; Oliveira, Joana M; de Grijs, Richard; Pennock, Clara M; et al.
ABSTRACT: We present a method to map the total intrinsic reddening of a foreground extinguishing medium via the analysis of spectral energy distributions (SEDs) of background galaxies. In this pilot study, we implement this technique in two distinct regions of the Small Magellanic Cloud (SMC) – the bar and the southern outskirts – using a combination of optical and near-infrared ugrizYJK s broad-band imaging. We adopt the lephare χ 2 -minimization SED-fitting routine and various samples of galaxies and/or quasi-stellar objects to investigate the intrinsic reddening. We find that only when we construct reddening maps using objects classified as galaxies with low levels of intrinsic reddening (i.e. ellipticals/lenticulars and early-type spirals), the resultant maps are consistent with previous literature determinations, i.e. the intrinsic reddening of the SMC bar is higher than that in the outer environs. We employ two sets of galaxy templates – one theoretical and one empirical – to test for template dependences in the resulting reddening maps and find that the theoretical templates imply systematically higher reddening values by up to 0.20 mag in E ( B − V ). A comparison with previous reddening maps, based on the stellar components of the SMC, typically shows reasonable agreement. There is, however, significant variation amongst the literature reddening maps as to the level of intrinsic reddening associated with the bar. Thus, it is difficult to unambiguously state that instances of significant discrepancies are the result of appreciable levels of dust not accounted for in some literature reddening maps or whether they reflect issues with our adopted methodology.